2020
DOI: 10.3892/or.2020.7692
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑590 inhibits migration, invasion and epithelial‑to‑mesenchymal transition of esophageal squamous cell carcinoma by targeting low‑density lipoprotein receptor‑related protein 6

Abstract: MicroRNA-590 (miR-590) has been revealed as a tumor suppressor, while low-density lipoprotein receptor-related protein 6 (LRP6) is considered to act as a tumor promoter. However, their roles and underlying molecular regulatory mechanisms in esophageal squamous cell carcinoma (ESCC) have yet to be fully elucidated. Therefore, the present study aimed to investigate these mechanisms. The expression levels of miR-590 and LRP6 in human ESCC samples and cell lines were determined using reverse transcription-quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…miRNAs are short RNAs with a length of 20–25 nucleotides ( 39 ). They can inhibit or degrade their target mRNAs by binding to the 3′non-coding region of their target gene mRNA ( 18 , 19 ). It has been reported that miRNAs are involved in a series of important processes, such as tumor proliferation, invasion and migration ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are short RNAs with a length of 20–25 nucleotides ( 39 ). They can inhibit or degrade their target mRNAs by binding to the 3′non-coding region of their target gene mRNA ( 18 , 19 ). It has been reported that miRNAs are involved in a series of important processes, such as tumor proliferation, invasion and migration ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that non-coding RNAs, such as long non-coding RNAs (lncRNAs) and microRNAs (miRNAs/miRs), play important roles in the development and progression of tumors (12)(13)(14). lncRNAs and miRNAs can influence the development of tumors by regulating physiological processes, such as cell proliferation and migration, apoptosis and autophagy (15)(16)(17)(18)(19). To the best of our knowledge, previous studies have not investigated whether lncRNAs and miRNAs enhance or affect the anticancer activity of lutein on breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs exert their biological functions by regulating the expression of their target genes at the transcriptional or post-transcriptional level (44). For example, it has been determined that HDAC4 is regulated by miR-200b-3p, miR-206, miR-29b and miR-873-3p (45)(46)(47)(48).…”
Section: Circ-lrp6 Contributes To Osteosarcoma Progression By Regulat...mentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are a kind of endogenous non‐coding small molecule single‐stranded RNA, with length generally between 19 and 24 nt; they mainly affect cell development, differentiation, proliferation, and apoptosis 25–28 . For instance, miR‐590 repressed the epithelial–mesenchymal transition (EMT) process by regulating LRP6 in esophageal squamous‐cell carcinoma 29 ; miR‐1 was proven to inhibit the malignancy of breast cancer stem cells by mediating Evi‐1 30 . MicroRNA‐122‐5p (miR‐122‐5p) acts as a tumor suppressor in ovarian, bile duct, and gastric cancers, glioma, and nasopharyngeal carcinoma 31–36 …”
Section: Introductionmentioning
confidence: 99%